Preliminary toxicity test and phytochemical screening of Sargassum Polycystum crude extracts from marine macroalgae / Norhayati Daud ... [et al.] - Daud, Norhayati; Mohd Noor, Nor Nafizah; Alimon, Hasimah; Abdul Rashid, Nursuhaidah (Universiti Teknologi MARA, Pulau Pinang, 2015)
Sargassum polycystum is a species of brown algae (Phaeophyta). Some recent studies have found many uses of this algae, one of them is for medicine. In this study, crude hexane, dichloromethane and methanol extracts of Sargassum polycystum were tested for toxicity activity and screened for its principal chemical substances. The toxicity test was done using Brine Shrimp Lethality (BSL) test against Artemia salina Leach. The results of this study showed the LC50 value of methanol extract was 295.12 mgml-1, while both hexane and dichloromethane extracts were 275.42 mgml-1. The BSL test exhibited no significant toxicity against A.salina. Phytochemical screening shows S. polycystum contained non polar and polar components. As the conclusion, S. polycystum contained secondary metabolites that are not toxic to A. salina and they are not a potential source for toxicity.